Characterization and seasonal changes in LHβ and FSHβ mRNA of Rhinella arenarum (Amphibia, Anura) - Volonteri, María Clara (2013)
In anurans, two types of gonadotropins were described in several species of Ranidae and Pipidae families but only in one of the Bufonidae family. Rhinella arenarum is a bufonid that have the lowest concentration of plasma androgens during the breeding. The objective of this paper was to characterize the cDNA sequence of β subunit of LH and FSH from toad pituitary and study seasonal variation in gonadotropins mRNA using quantitative real-time RT-PCR. The LHβ cDNA is a 636 bp sequence containing an open reading frame (ORF), 45 bp of 5′-untranslated region (UTR) and 174 bp of 3′-UTR. The ORF encodes for a signal peptide of 26 amino acids and a mature protein of 113 amino acids with one N-glycosylation site at the 34th position. The FSHβ cDNA sequence is a 535 bp fragment containing an ORF, 8 bp of 5′-UTR and 152 bp of 3′-UTR. The ORF encodes for a signal peptide of 20 amino acids and a mature protein of 104 amino acids with two N-glycosylation sites at 25th and 42nd positions. Multiple alignments of aminoacid deduced sequences of LHβ and FSHβ (teleosts, amphibians, birds, mammals) showed that all the tetrapods studied conserve 12 cysteins and one (LH) or two (FSH) N-Glycosylation sites. LHβ is closer to teleosts than to mammals and birds while FSHβ is closer to mammals. The analysis of seasonal changes in LHβ and FSHβ mRNA indicates that transcript levels have seasonal variations and that the profile of androgens is opposite to that of the gonadotropins mRNA.